CT Angiography Evaluation of Unusual Transorbital Penetrating Injury: A Toothbrush. Issue 2 (19th February 2013) - Atay, Musa; Alkan, Alpay; Hanimoglu, Hakan; Sharifov, Rasul; Kilicarslan, Rukiye; Aralasmak, Ayse
ABSTRACT Orbital penetrating injuries may cause significant harm to optic nerves and eyeball as well as to the brain and cerebral vasculature. Defining surrounding neurovascular structures by CT angiography (CTA) is important for surgical removal. We present an uncommon case of a 3‐year‐old child with a penetrating orbital injury caused by a toothbrush. To the best of our knowledge, there is no report orbital injury with a toothbrush so far.